Model Penta Helix dalam Upaya Pengembangan Desa Wisata Agro Kubu Gadang Kota Padang Panjang - Arrahman, Tharriq; Suwaryono, Ixora Lundia (Jurnal Administrasi dan Kebijakan Publik, 2024)
Tourism become a leading sector for development in Indonesia. The Development of the tourism industry is carried out comprehensively in almost all regions in Indonesia, one of the potential region is Kubu Gadang tourist village, Padang Panjang, West Sumatera. This research used theory penta helix by (Carayannis & Campbell, 2011) and tourism development theory by (Sharpley & Telfer, 2008) with output indicators including: Environmental Development, Economic and Political Development, Social-Cultural Development, Community Roles Development dan Human Resources Development. The result show that several tourism development indicators have been implemented, but there is still minimal training to Pokdarwis, and there is still no special budgeting for developing teourst villages. Because tourism development is not a main focus from Youth, Sports and Tourism Departement Padang Panjang (Disporapar). Disporapar as leading sector has establishing all collaborations with stakeholders, but there is no specific division to authority. Which means there is still an overlap in division of tasks and authority in developing this tourist village.